Activity of TNT: a phase 2 study using talimogene laherparepvec, nivolumab and trabectedin for previously treated patients with advanced sarcomas (NCT# 03886311) - Chawla, Sant P.; Tellez, Walter Andree; Chomoyan, Hripsime; Valencia, Chrysler; Ahari, Amir; Omelchenko, Nadezhda; Makrievski, Stefan; Brigham, Don A.; Chua-Alcala, Victoria; Quon, Doris; Moradkhani, Ania; Gordon, Erlinda M. (Frontiers in Oncology, 2023)
Background Intratumoral injection of talimogene laherparepvec evokes a cytotoxic immune response. Therefore, the combination of talimogene laherparepvec with trabectedin and nivolumab may have synergistic effects in advanced sarcomas. Patients and methods This phase 2 trial was conducted from May 30, 2019 to January 31, 2022. Endpoints: Primary: Progression free survival rate at month 12. Secondary: Best overall response, progression free survival rate at 6 and 9 months, overall survival rate at 6, 9, and 12 months, incidence of conversion of an unresectable tumor to a resectable tumor, and incidence of adverse events. Eligible patients had to be ≥ 18 years of age, have advanced histologically proven sarcoma, at least 1 previous chemotherapy regimen, and at least one accessible tumor for intratumoral injection. Treatment: Trabectedin intravenously (1.2 mg/m2 q3 weeks), nivolumab intravenously (3 mg/kg q2 weeks), and intratumoral talimogene laherparepvec (1x108 plaque forming units/ml q2 weeks). Results Median time of follow-up: 15.2 months. Efficacy analysis: Thirty-nine patients who had completed at least one treatment cycle and had a follow-up computerized tomography were evaluable for efficacy analysis. Median number of prior therapies: 4 (range 1-11). Progression free survival rate at month 12, 36.7%. Confirmed Best Overall Response by Response Evaluation Criteria in Solid Tumors v1.1 = 3 partial responses, 30 stable disease, 6 progressive disease. Best Overall Response Rate, 7.7%, Disease Control Rate, 84.6%; median progression free survival, 7.8 (95% Confidence Intervals: 4.1-13.1) months; 6-, 9-, 12-month progression free survival rates, 54.5%/45.9%/36.7%; median overall survival 19.3 (95% Confidence Intervals: 12.8 -.) months; 6-, 9- and 12-month overall survival rate, 86.9%/73.3%/73.3%. One patient had a complete surgical resection. Fifty percent of patients had a ≥ grade 3 treatment related adverse events which included anemia (6%), thrombocytopenia (6%), neutropenia (4%), increased alanine transaminase (4%), decreased left ventricular ejection fraction (4%), dehydration (4%), hyponatremia (4%). Conclusions Taken together these data suggest that the TNT regimen is effective and safe for advanced previously treated sarcomas, and is worth being further studied in a randomized phase 3 trial as first- or second- line treatment for patients with advanced sarcomas.